Pembangunan Aplikasi Manajemen Event Gereja KGC Malang Berbasis Web - Samuel Ricko Perdana Putra; Fajar Pradana; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Event is an activity which held for a public meeting or inviting many people for celebration, education, and marketing. Kingdom Generation Community (KGC) Malang is a youth people church under the authority of the Indonesian Bethel Church (GBI) Representative of Christ Kingdom (ROCK). KGC Malang has a purpose to reaching out and develop youth people to be a positive impact on their environment. To achieve this goal, KCG Malang has many events. However, in the execution of the event, KGC Malang has many problems, such as the absence report, there is no recording process for each member growth. Eventually, hard for the leader make the right decisions for an event, placing a member to the right position because there is no data record. Base on these problems has created an application to manage many activities of KGC Malang from planning until reporting or evaluating, and make a centralized member data collection system than can be accessed by leaders. This study is using SDLC Waterfall. The research is started with an interview and engineering needs. This phase produces 33 functional requirements and one non-functional requirement with 4 actors. Sequence diagram, class diagram, user interface design, and database design is the result of the design phase as a foundation for the implementation phase. This application development uses HTML, CSS, Javascript, and PHP with frameworks Laravel and VueJS. The system tested using unit testing which tests 3 primary functions of system and 3 test case with result 100% valid, validation testing to test 33 functional requirement and 33 test case with result 100% valid, and compatibility testing to test the non-functional requirement and the result there is no significant issues which impacted for functionality of application.